Information goals for a regional ground water quality monitoring system for the San Luis Valley - Bagenstos, Dennis J., author; Ward, Robert C., advisor; Loftis, Jim C., advisor; Durnford, Deanna S., committee member; Smith, Freeman, committee member (Colorado State University. Libraries, 1994)
The residents of the San Luis Valley of Colorado are dependent on ground water resources for agriculture, the economic base of the region, as well as most of their drinking water. The quality of this water, as a result of its extensive use, has become a concern in recent years. This concern has been expressed not only by local residents, but also the general public, as demonstrated by the numerous state and federal laws that address ground water quality issues. This concern tends to be addressed in a rather piecemeal fashion, particularly with regard to efforts to measure water quality in the San Luis Valley. Each concern and law appears to require its own separate monitoring program. Can the information needs generated by both local concerns and legal mandates be integrated into a more coherent set of information goals that would guide a unified monitoring program? What information would such a program need to produce? The purpose of this research was to develop a set of water quality "Integrated Information Goals" defined as the integration of those information needs extrapolated from the laws, regulations, and groups involved in water quality management in the Valley. In order to develop these information goals, the following tasks were defined: 1) Examine, through the review and identification of federal, state and local laws, regulations, implementing agencies, and concerned groups, the current structure of nonpoint source pollution management with respect to ground water quality in the San Luis Valley. 2) Based on the review in (1) above, define information goals for a monitoring design for the San Luis Valley. 3) Specify the Integrated Information Goals needed to support ground water quality management in the San Luis Valley. Upon completion of these tasks, five information goals were defined: 1. Baseline water quality of the shallow unconfined and the deep confined aquifers, 2. Source impacts to correlate water quality problems with land use practices, 3. Water table levels, 4. Water quality trend detection, 5. BMP analysis. Options for implementation of a monitoring system were also presented.
Keywords: Water resources development -- Information services -- San Luis Valley (Colo. and N.M.); Water quality -- Information services -- San Luis Valley (Colo. and N.M.)